Prediction of reproductive outcomes according to different serum anti-Müllerian hormone levels in females undergoing intracystoplasmic sperm injection - Brugo Olmedo, Santiago (2013)
Serum anti-Müllerian hormone (AMH) is a reliable marker of ovarian reserve, and it has been shown to be correlated with reproductive outcomes in grouped analyses. However, practical data is scarce for the physician and the patients to predict these outcomes in an individual couple according to serum AMH measured prior to assisted reproduction technology (ART) procedures.